Quantity determination of Recorcinol by coupling reaction with diazotized Of 4-aminacet phenone (Journal of the College of Basic Education, 2022)
Development of an analytical method to determine Recorcinolcompound by coupling reaction for diazotized solution of 4- aminacetphenone in the presence of buffer solution NasHPO, (pH= 10.8) to give acompound with a single azo dye salt having orange color soluble in waterwith high absortivity at a wave length 449 nm , an early study to have aperfect optimum condition was made for the determination. A calibrationcurve for a range of concentration (5-75)pm was taken and the value ofmolar absortivity was 1.5*10° L.mol'.cm™ with a relative standarddeviation more than 1.26% and a recovery 98.77% .As we study the natureof the azo dye by mole fraction method, from the practical value we foundthat the mole fraction of the dye compound is 1:1(Recorcinol: 4-aminacetphenone) and the stability factor reach to 1.4*10° L.mol’.